Development of a flexible anode for lithium-ion batteries from electrospun carbon-magnetite composite microfibers (2022)
ABSTRACT : The development of a binder-free material is gaining ground as a flexible anode in lithium-ion batteries due to the higher specific capacity and possibilities of usage in portable appliances. In this work, magnetite nanoparticles (Fe3O4-NPs) were incorporated into carbon microfibers (CMFs) by electrospinning technique to improve the specific capacity of active material, retaining the high flexibility of the CMFs. The composite active material (CMFs-Fe3O4) was characterized by Raman spectroscopy, Thermogravimetric analyses (TGA), and transmission electron microscopy (TEM) to determine the composition, structure, and morphology of the composite. Electrochemical tests were done to evaluate the performance of the composite material as an anode in lithium-ion batteries. Fe3O4-NPs with particle sizes from 30 to 40 nm were incorporated into CMFs (800 nm), and the TEM images showed a homogeneous distribution of Fe3O4-NPs. The electrochemical tests evidenced that magnetite incorporation increases the specific capacity by 42% on the first cycle and 20% on the 50th cycle. Similarly, the Coulombic efficiency increases by 20% in the composite material.